Penerapan Contextual Teaching and Learning untuk Meningkatkan Motivasi Belajar Matematika Siswa MTs - Firmansah, Tomi Arjun; Sulistyaningrum, Heny (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
The low learning motivation of eighth-grade students at MTs Al-Mufazah Sukolilo Bancar Tuban formed the background of this study, as indicated by a pre cycle average motivation score of 63.9 (moderate category), with only 17% of students reaching the high category. This condition was driven by the dominance of conventional, teacher-centered learning that lacked relevance to students' real life contexts. This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model within a deep learning framework in mathematics instruction, to analyze the improvement of students' learning motivation, and to evaluate the achievement of high motivation indicators in each cycle. This research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles, each comprising planning, action, observation, and reflection stages. The subjects were 29 eighth-grade students of MTs Al-Mufazah in the 2025/2026 academic year. Data were collected through a learning motivation questionnaire, classroom observation sheets, and teacher interviews, then analyzed using a descriptive comparative method. The results showed a significant and sustained increase in motivation: the average score rose from 63.9 (pre cycle) to 71.7 (cycle I) and 81.7 (cycle II). By the end of cycle II, 97% of students had reached the moderately high or high category, exceeding the 75% success indicator, with 66% classified as high (score ≥85) and 31% as moderately-high. These findings indicate that the CTL model, which contextualizes mathematics with students' real-life experiences, effectively enhances learning motivation, making mathematics learning more meaningful and deep